DEVELOPMENT OF SOCIAL RESPONSIBILITY OF MILITARY EDUCATION STUDENTS - A. Uzokov (Scholar Express Journal, 2022)
Pedagogical psychological aspects of the development of social responsibility in students were determined based on an empirical assessment of the relationship between the qualities of determining the sense of social responsibility in students (cognitive-emotional, intellectual-motivational, axiological-prognostic) with personal social experience and position, such as humanitarianism, entrepreneurship, teamwork.
Keywords: Education; patriotism; activity; regularity